2022
DOI: 10.21037/jgo-22-1158
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose apatinib combined with camrelizumab and the SOX regimen in the neoadjuvant treatment of locally advanced gastric/gastroesophageal junction adenocarcinoma (SPACE-neo): a protocol for an open-label, single-arm, clinical trial

Abstract: Background: Neoadjuvant chemotherapy with S-1 plus oxaliplatin (SOX regimen) has shown promising results in pathological response rate and survival rate in patients with locally advanced resectable gastric cancer (LAGC). We previously carried out the SPACE study to assess efficacy and safety of low-dose apatinib combined with camrelizumab and the SOX regimen as a first-line treatment of advanced gastric/ gastroesophageal junction adenocarcinoma (AGC/GEJC). The preliminary results demonstrated a high objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that apatinib could shorten the onset time and potentiate the anti-tumor effects of camrelizumab across various types of solid tumors, including advanced hepatocellular carcinoma, cervical cancer, lung cancer, and osteosarcoma ( 18 , 24 - 27 ). Peng et al investigated the effects of camrelizumab in combination with CAPOX followed by camrelizumab plus apatinib therapy on advanced GC patients and revealed encouraging anti-tumor activity and manageable toxicity ( 28 ), Pan et al also evaluated the efficacy and safety of apatinib in combination with camrelizumab and the SOX regimen as a first-line treatment for advanced gastric/gastro-oesophageal junction adenocarcinoma and the results showed a high objective response rate (ORR) ( 29 ). Therefore, camrelizumab in combination with apatinib has strong clinical data to support the treatment of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that apatinib could shorten the onset time and potentiate the anti-tumor effects of camrelizumab across various types of solid tumors, including advanced hepatocellular carcinoma, cervical cancer, lung cancer, and osteosarcoma ( 18 , 24 - 27 ). Peng et al investigated the effects of camrelizumab in combination with CAPOX followed by camrelizumab plus apatinib therapy on advanced GC patients and revealed encouraging anti-tumor activity and manageable toxicity ( 28 ), Pan et al also evaluated the efficacy and safety of apatinib in combination with camrelizumab and the SOX regimen as a first-line treatment for advanced gastric/gastro-oesophageal junction adenocarcinoma and the results showed a high objective response rate (ORR) ( 29 ). Therefore, camrelizumab in combination with apatinib has strong clinical data to support the treatment of GC.…”
Section: Discussionmentioning
confidence: 99%